Personalized therapeutics for levofloxacin: a focus on pharmacokinetic concerns - Gao CH; Yu LS; Zeng S; Huang YW; Zhou Q (Dove Medical Press, 2014)
Chu-Han Gao,1 Lu-Shan Yu,2 Su Zeng,2 Yu-Wen Huang,1 Quan Zhou11Department of Pharmacy, the Second Affiliated Hospital, School of Medicine, 2Department of Pharmaceutical Analysis and Drug Metabolism, College of Pharmaceutical Sciences, Zhejiang University, Hangzhou, Zhejiang Province, People's Republic of ChinaBackground: Personalized medicine should be encouraged because patients are complex, and this complexity results from biological, medical (eg, demographics, genetics, polypharmacy, and multimorbidities), socioeconomic, and cultural factors. Levofloxacin (LVX) is a broad-spectrum fluoroquinolone antibiotic. Awareness of personalized therapeutics for LVX seems to be poor in clinical practice, and is reflected in prescribing patterns. Pharmacokinetic–pharmacodynamic studies have raised concerns about suboptimal patient outcomes with the use of LVX for some Gram-negative infections. Meanwhile, new findings in LVX therapeutics have only been sporadically reported in recent years. Therefore, an updated review on personalized LVX treatment with a focus on pharmacokinetic concerns is necessary.Methods: Relevant literature was identified by performing a PubMed search covering the period from January 1993 to December 2013. We included studies describing dosage adjustment and factors determining LVX pharmacokinetics, or pharmacokinetic–pharmacodynamic studies exploring how best to prevent the emergence of resistance to LVX. The full text of each included article was critically reviewed, and data interpretation was performed.Results: In addition to limiting the use of fluoroquinolones, measures such as reducing the breakpoints for antimicrobial susceptibility testing, choice of high-dose short-course of once-daily LVX regimen, and tailoring LVX dose in special patient populations help to achieve the validated pharmacokinetic–pharmacodynamic target and combat the increasing LVX resistance. Obese individuals with normal renal function cleared LVX more efficiently than normal-weight individuals. Compared with the scenario in healthy subjects, standard 2-hour spacing of calcium formulations and oral LVX was insufficient to prevent a chelation interaction in cystic fibrosis patients. Inconsistent conclusions were derived from studies of the influence of sex on the pharmacokinetics of LVX, which might be associated with sample size and administration route. Children younger than 5 years cleared LVX nearly twice as fast as adults. Patients in intensive care receiving LVX therapy showed significant pharmacokinetic differences compared with healthy subjects. Creatinine clearance explained most of the population variance in the plasma clearance of LVX. Switching from intravenous to oral delivery of LVX had economic benefits. Addition of tamsulosin to the LVX regimen was beneficial for patients with bacterial prostatitis because tamsulosin could increase the maximal concentration of LVX in prostatic tissue. Coadministration of multivalent cation-containing drugs and LVX should be avoided. For patients receiving warfarin and LVX concomitantly, caution is needed regarding potential changes in the international normalized ratio; however, it is unnecessary to seek alternatives to LVX for the sake of avoiding drug interaction with warfarin. It is unnecessary to proactively reduce the dose of cyclosporin or tacrolimus when comedicated with LVX. Transporters such as organic anion-transporting polypeptide 1A2, P-glycoprotein, human organic cation transporter 1, and multidrug and toxin extrusion protein 1 are involved in the pharmacokinetics of LVX.Conclusion: Personalized LVX therapeutics are necessary for the sake of better safety, clinical success, and avoidance of resistance. New findings regarding individual dosing of LVX in special patient populations and active transport mechanisms in vivo are opening up new horizons in clinical practice.Keywords: drug interactions, fluoroquinolone resistance, individual dosing, patient complexity, personalized medicine, pharmacokinetics, pharmacodynamics, therapeutics